2009
DOI: 10.1530/eje-08-0709
|View full text |Cite
|
Sign up to set email alerts
|

Gestational thyroid function abnormalities in conditions of mild iodine deficiency: early screening versus continuous monitoring of maternal thyroid status

Abstract: Objective: To longitudinally evaluate the timing of maternal thyroid underfunction occurrence in mildly iodine-deficient (ID) pregnant women, and ultimately assess the benefit of thyroid function testing at early gestation only in identifying maternal thyroid underfunction. Participants/methods: Serum free-thyroxine and TSH were measured in 220 consecutive women once in early pregnancy (by week 12) and twice per trimester subsequently. Anti-thyroperoxidase and antithyroglobulin were also determined at initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 32 publications
5
40
0
3
Order By: Relevance
“…One could argue that the identification and treatment of hypothyroidism in the first antenatal visit, as recommended by the guidelines (4, 7), may be too late to prevent the associated adverse effects; however, implementing systemic screening of thyroid function in all women contemplating pregnancy would be an enormous challenge for any country. Although a recent study has suggested that, if screening is limited to first trimester, over 40% pregnant women with hypothyroidism could be missed (19), there was no agreement amongst responders whether thyroid function tests should be routinely repeated in later stages of pregnancy if the initial screening was normal.…”
Section: Recommendationsmentioning
confidence: 99%
“…One could argue that the identification and treatment of hypothyroidism in the first antenatal visit, as recommended by the guidelines (4, 7), may be too late to prevent the associated adverse effects; however, implementing systemic screening of thyroid function in all women contemplating pregnancy would be an enormous challenge for any country. Although a recent study has suggested that, if screening is limited to first trimester, over 40% pregnant women with hypothyroidism could be missed (19), there was no agreement amongst responders whether thyroid function tests should be routinely repeated in later stages of pregnancy if the initial screening was normal.…”
Section: Recommendationsmentioning
confidence: 99%
“…the variables measured and their cut-off values, are more controversial (16). In addition, the yield of screening may be influenced by regional differences, namely, by iodine sufficiency (25).…”
Section: Consensus Guideline Risk Factormentioning
confidence: 99%
“…One could argue that the identification and treatment of hypothyroidism in the first antenatal visit may be too late to prevent the associated adverse effects; however, implementing systemic screening of thyroid function in all women contemplating pregnancy would be an enormous challenge, especially for developing countries of Asia. A recent study has suggested that, if screening is limited to first trimester, over 40% of pregnant women with hypothyroidism could be missed [12] and 68% of our responders agreed that thyroid function tests should be repeated in later stages of pregnancy if the initial screening was normal, 27% routinely and 41% in the presence of thyroid antibodies.…”
Section: Discussionmentioning
confidence: 72%
“…countries with ten or more responders included: Iran (44), Indonesia (43), Philippines (40), Taiwan (38), Malaysia (23), Japan (14), Singapore (12), India (11), Thailand (11), and Srilanka (10).…”
mentioning
confidence: 99%